ASSESSING THE SUITABILITY OF F1 HYBRID VARIETIES IN GROWING CUCUMBER IN GREENHOUSES FOR THE EFFECTIVE CONTROL OF DOWNY MILDEW DISEASE (Conferencea, 2023)
Food safety is one of the most crucial tasks facing all countries worldwide. In the mentioned article, the level of resistance to wheat rust disease in 50 selected varieties, obtained from both local and foreign germplasm, has been assessed for suitability in cultivation for hot climates, and the results of the evaluation have been highlighted.